Oncological relevance of major hepatectomy with inferior vena cava resection for intrahepatic cholangiocarcinoma. Issue 9 (September 2021) - Palen, Anais; Garnier, Jonathan; Hobeika, Christian; Ewald, Jacques; Gregoire, Emilie; Delpero, Jean-Robert; Le Treut, Yves P.; Turrini, Olivier; Hardwigsen, Jean
Abstract: Background: This study aimed to investigate the short- and long-terms outcomes of patients undergoing major hepatectomy (MH) with inferior vena cava (IVC) resection for intrahepatic cholangiocarcinoma (ICC). Methods: Data from all patients who underwent MH for ICC with or without IVC resection between 2010 and 2018 were analysed retrospectively. Postoperative outcomes, overall survival (OS), and recurrence-free survival (RFS) were compared in the whole population. A propensity score matching (PSM) analysis and an inverse probability weighting analysis (IPW) were performed to assess the influence of IVC resection on short- and long-terms outcomes. Results: Among the 78 patients who underwent MH, 20 had IVC resection (IVC patients). Overall, the mortality and severe complication rate were 8% and 20%, respectively. IVC patients required more extended hepatectomies (p = 0.001) and had increased rates of transfusions (p = 0.001), however they did not experience increased postoperative morbidity, even after PSM. The 1-, 3- and 5-years OS and DFS were 78%, 45%, and 32% and 48%, 20%, and 16%, respectively. IVC was not associated with decreased OS (p = 0.52) and/or RFS (p = 0.85), even after IPW. Conclusion: MH with IVC resection for ICC seems to provide acceptable short- and long-term results in a selected population of patients.